Prevalence of Musculoskeletal Disorders among Dental Practitioners in Lahore - Ahmad Liaquat, Ehsan Ul Haq, Muhammad Abbas, Sheikh Saadullah Waleen, Mahnoor Sikandar, Tahmasub Faraz Tayyab, Rehan Qamar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Literature reviews have shown a high prevalence of musculoskeletal disorders (MSD) among dental practitioners. Local data on the prevalence of MSD among dentists are scarce. Aim: To determine the prevalence and distribution of MSD in various cities of Pakistan and to find the distribution of related symptoms in different parts of the body. Methods: A cross-sectional descriptive study in which a self-administered questionnaire- the Standardized Nordic Questionnaire was used to assess the musculoskeletal symptoms among dental practitioners. The inclusion criteria consisted of dentists currently in practice and fresh graduates’ in house job. Retired dentists and dental students in their undergraduate years were excluded from this study. A total of 138 participants recorded their responses in the online survey over a period of two weeks. Statistical analyses were performed using the SPSS Version 23.0. Results: The most commonly affected area was the neck region (72.10%) followed by shoulders (62.50%) and lower back (54.81%). The least prevalent symptoms were reported in ankles and feet (17.31%) and knees (15.38%). A higher number of female respondents experienced trouble in the neck (p=0.037). Similarly, a high number of female respondents experienced trouble in shoulders (p= 0.040). In contrast, a higher number of male respondents experienced trouble in their hands/wrists (p=0.032). Conclusion: A high prevalence of MSD exists among dental practitioners which affects their daily practice. Further studies are needed to identify the specific risk factors for MSD to introduce effective remedial measures. Keywords: Musculoskeletal disorders, prevalence, dental practitioners, ergonomics